Treatment of refractory ascites with an automated low‐flow ascites pump in patients with cirrhosis. Issue 10 (21st September 2017) - Stirnimann, G.; Berg, T.; Spahr, L.; Zeuzem, S.; McPherson, S.; Lammert, F.; Storni, F.; Banz, V.; Babatz, J.; Vargas, V.; Geier, A.; Stallmach, A.; et al.
Summary: Background: Refractory ascites (RA) is a frequent complication of cirrhosis, requiring large volume paracentesis or placement of a transjugular intrahepatic portosystemic shunt (TIPSS). The automated low‐flow ascites pump (alfapump, Sequana Medical AG, Zurich, Switzerland) is an innovative treatment option for patients with RA. Aim: To assess safety and efficacy of this treatment in patients with a contraindication to TIPSS. Methods: Fifty‐six patients (43 males; mean age 62 years) from centres in Germany, Switzerland, UK and Spain were included and followed for up to 24 months. Complications, device deficiencies, paracentesis frequency and patient survival were recorded. Results: At the time of this analysis, 3 patients completed the 24‐month observation period, monitoring of 3 was ongoing, 9 underwent liver transplantation, 17 patients were withdrawn due to serious adverse events and 23 patients died. Most frequently observed technical complication was blocking of the peritoneal catheter. Twenty‐three pump‐related reinterventions (17 patients) and 12 pump exchanges (11 patients) were required during follow‐up. The pump system was explanted in 48% of patients (in 17 patients due to serious adverse events, in 9 at the time of liver transplantation and in 1 due to recovery from RA). Median frequency of paracentesis dropped from 2.17 to 0.17 per month. Conclusions: The alfapump can expand therapeutic options for cirrhotic patients with RA. Continuous drainage of ascites in a closed loop automated system led to significant reduction in paracentesis frequency. Technical and procedural improvements are required to reduce the rate of adverse events and reinterventions. https://clinicaltrials.gov/ct2/show/NCT01532427 Abstract : Linked Content This article is linked to Macdonald and Jalan and Stirnimann and De Gottardi papers and Weil et al papers. To view these articles visithttps://doi.org/10.1111/apt.14390, https://doi.org/10.1111/apt.14415, https://doi.org.10.1111/apt.14440 andhttps://doi.org.10.1111/apt.14500 .